Collaborative healthcare system between clinics and hospitals in Malaysia - Ahmad Dahlan, Abdul Rahman; Abdulatif, Zaidoon Khalil; Mahmoud, Ismail; Aydin, Muhammed (P Kulkarni, 2011)
Healthcare organizations in over the world had dynamic changes. They have contributed to intensify competitive activity between healthcare providers. These changes have forced the organizations to consider wide improvement of their activities and to adopt the use of new technologies in all the organizations’ operations. Recently, there have been high demands for collaborative medical services between clinics and hospital medicines in the world. This paper proposes a model; diagrams are enabled collaboration in medicine systems between hospitals and clinics with attaching that system under the ministry of health in Malaysia.